The nightingale - Hannah, Kristin (New York: St. Martin's Griffin, 2015)
"Viann and Isabelle have always been close despite their differences. Younger, bolder sister Isabelle lives in Paris while Viann lives a quiet and content life in the French countryside with her husband Antoine and their daughter. When World War II strikes and Antoine is sent off to fight, Viann and Isabelle's father sends Isabelle to help her older sister cope. As the war progresses, it's not only the sisters' relationship that is tested, but also their strength and their individual senses of right and wrong. With life as they know it changing in unbelievably horrific ways, Viann and Isabelle will find themselves facing frightening situations and responding in ways they never thought possible as bravery and resistance take different forms in each of their actions. Vivid and exquiste in its illumination of a time and place that was filled with great monstrosities, but also great humanity and strength, Kristin Hannah's novel will provoke thought and discussion that will have readers talking long after they turn the last page"--
Keywords: Historical fiction